Structural and durability properties of hydraulic lime–pozzolan concretes. (September 2015) - Grist, E.R.; Paine, K.A.; Heath, A.; Norman, J.; Pinder, H.
Abstract: This paper discusses the results of a suite of tests designed to assess the structural and durability characteristics of hydraulic lime–pozzolan concretes. Specifically, this paper reports on the rate of strength development, elastic modulus, linear shrinkage and rate of carbonation of four hydraulic-lime–pozzolan concretes. The purpose of this investigation was to ascertain the technical feasibility of producing high strength concretes using hydraulic lime and pozzolans as an alternative binder to Portland cement. Results have demonstrated that 28-day compressive cube strengths of 35 MPa can be attained by water-cured lime–pozzolan concretes. The results are presented alongside comparable test results for Portland-cement (CEMI) and blastfurnace cement (CIII/A) concretes. Similarities and differences in material characteristics are discussed in terms of fundamental material properties and in terms of the emergent threats and opportunities for the potential development of these novel concretes.